THE INFLUENCE OF TIC'S IN UNIVERSITY TEACHING AT THE FACULTY ACCOUNTING STUDIES OF SAN MARCOS UNIVERSITY - Vergara Moncada, Raúl Jesús (2010)
At present the teachers of the University System we need to know the multiple concepts that are in use in the world of the New Technologies of Information and Communication (NTICs), for which the present work of investigation the university student tries to clarify some concepts relative to the above mentioned means in the process of Education Learning across technological means as the contributions and the problematics of the TICs, the Universities and the Use of the Web, as central element in a level of car learning, the action of the university teacher opposite to virtual environments and finally a survey to the Teachers of the Faculty of Countable Sciences of the UNMSM, conclusions and recommendations.